Charismatic Authority and Digital Resistance: The Role of Kyais in Countering Takfiri Radicalism in Society - Dinda Febrianti Putri; Babun Suharto (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2025)
The increasing spread of digital da’wah based on takfiri doctrine has threatened the religious stability and social cohesion of Muslims in Indonesia. This study aims to analyze the role of kyais' charismatic authority in building digital resistance against takfiri radicalism in Indonesia's networked society. Using a qualitative case study design, data were collected through in-depth interviews with kyais, students, media managers, and congregations; observations of Islamic boarding school activities; and documentation in the form of da’wah archives and digital publications from an Islamic boarding school that actively promotes Islamic moderation. The findings indicate that (1) the charisma of the kyai's knowledge dampens the effects of algorithmic radical content because the congregation trusts the kyai's explanations more than extreme digital narratives, (2) Islamic boarding school moderation shifts the congregation's religious discourse style from takfiri rhetoric to peaceful dialogue, and (3) the sanad of knowledge forms ideological resilience so that the congregation feels confident in the source of moderate teachings. The novelty of this research lies in the integration of charismatic authority and digital resistance as a model of deradicalization based on Islamic moderation. The implication is that Islamic boarding schools should expand their digital da’wah by emphasizing the charisma of their knowledge and sanad (traditional Islamic lineage), thereby strengthening the effectiveness of Islamic moderation in both online and offline spaces.